Dynamic Data Processing with Kaiman Filter - Kluga, A.; Kluga, J. (Elektronika ir Elektrotechnika, 2011)
In this work research results of dynamic data processing with adaptive Kalman filter are presented. In filtering process parameters of filter are change on results of difference between measuring and expected coordinate. Modeling results of adaptive Kalman filtering are comparing with classic Kalman filter. Modeling results using adaptive Kalman filtering for coordinate estimation shows that estimation error decrease in points when parameters of movement change very rapidly. Results of adaptive Kalman filter modeling and filter use for GPS receiver information processing are described. Ill. 11, bibl. 4 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.351